Associations between the oxytocin receptor gene (OXTR) and "mind-reading" in humans—An exploratory study. (February 2013) - Lucht, Michael J.; Barnow, Sven; Sonnenfeld, Christine; Ulrich, Ines; Grabe, Hans Joergen; Schroeder, Winnie; Völzke, Henry; Freyberger, Harald J.; John, Ulrich; Herrmann, Falko H.; Kroemer, Heyo; Rosskopf, Dieter
Abstract Background/aims: The application of intranasal oxytocin enhances facial emotion recognition in normal subjects and in subjects with autism spectrum disorders (ASD). In addition, various features of social cognition have been associated with variants of the oxytocin receptor gene (OXTR). Therefore, we tested for associations between mind-reading, a measure for social recognition and OXTR polymorphisms. Methods: 76 healthy adolescents and young adults were tested for associations between OXTR rs53576, rs2254298, rs2228485 and mind-reading using the "Reading the Mind in the Eyes Test" (RMET). Results: After Bonferroni correction for multiple comparisons, rs2228485 was associated with the number of incorrect answers when subjects evaluated male faces (P =0.000639). There were also associations between OXTR rs53576, rs2254298 and rs2228485 and other RMET dimensions according to P <0.05 (uncorrected). Conclusion: This study adds further evidence to the hypothesis that genetic variations in the OXTR modulate mind-reading and social behaviour.